Pengembangan modul berbasis riset pada mata kuliah kalkulus untuk meningkatkan kreativitas mahasiswa - Alfiani Athma Putri Rosyadi (STKIP PGRI Banjarmasin, 2018)
This study aims 1) Develop research-based modules on calculus courses, 2) Know the effectiveness of research-based modules in the calculus course, and 3) Know the improvement of student creativity after using research-based modules on the calculus course. This type of research is research and development (research and development). Subjects in this study are students of mathematics education program of Calculus Differential course 2018. Data collection methods used questionnaires, interviews, tests and observation sheets. Data analysis used data collection, data presentation and data reduction. The research of this research-based module on the calculus course was developed through the following stages: a) Preliminary Analysis, b) developing research-based modules, c) Validation of media and material experts, d) Revision of research-based modules, e) Implementation of research-based modules, Data collection and g) Data Analysis. This module was included in the effective category based on the assessment of the validator and student questionnaire. After used this module there is an increased in student creativity especially at the stage of originality. The development of this module was said to be effective because the results of expert validation scores and student questionnaire dissemination obtained a score of 3.67 in either category. To increase the creativity of students after using the research-based module can be seen from the results of student scores. The score before used the module was 73.47 and the score after used the module was 82.36